Self-assembly of diphenylalanine peptide with controlled polarization for power generation - Vu Nguyen (Nature Portfolio, 2016)
Piezoelectricity in diphenylalanine peptide nanotubes (PNTs) suggests an avenue towards green piezoelectric devices. Here the authors show ‘smart’ PNTs whose polarization can be controlled with an electric field, and a resultant power generator which harvests biomechanical energy with high power density.